2020
DOI: 10.1113/jp278790
|View full text |Cite
|
Sign up to set email alerts
|

Active cooling temperature required to achieve therapeutic hypothermia correlates with short‐term outcome in neonatal hypoxic‐ischaemic encephalopathy

Abstract: Key points Hypoxic‐ischaemic encephalopathy (HIE) affects 2–4/1000 live term births. Treatment with therapeutic hypothermia (TH) improves the long‐term neurodevelopmental outcome of neonates with moderate to severe HIE. However, early prediction of outcome still remains challenging, and no reliable and easily obtainable biomarker has been identified to date. Neonates with HIE display impaired thermoregulation, resulting in spontaneous hypothermia. The degree of cooling required to achieve TH may therefore act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
(54 reference statements)
1
16
0
3
Order By: Relevance
“…It has been shown that heat production estimated in this way correlates with HIE severity in adult patients after cardiac arrest 27,28 . Similar results were obtained in the study of neonates with PA 29 . It should, however, be underlined that considering only the water-cooling process, some other heat transfer mechanisms have been ignored.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…It has been shown that heat production estimated in this way correlates with HIE severity in adult patients after cardiac arrest 27,28 . Similar results were obtained in the study of neonates with PA 29 . It should, however, be underlined that considering only the water-cooling process, some other heat transfer mechanisms have been ignored.…”
supporting
confidence: 89%
“…Mietzsch 29 also noted that in newborns with PA treated by TH, temperature of the active cooling medium correlates with severity of brain injury diagnosed with Magnetic Resonance Imaging (MRI). Namely, the temperature of the cooling medium required to keep patients' at target temperature of 33.5 °C was found and proposed to be a prognostic factor for neurological injuries in neonates with HIE.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Спонтанну гіпотермію вважають проявом порушень чи зміни схеми терморегуляції у дітей із постгіпоксичними ураженнями ЦНС. У новонароджених із помірною та тяжкою ГIE спонтанно виникає гіпотермія, причому в дітей із тяжкою ГІЕ температура тіла була нижча порівняно з немовлятами з помірною ГІЕ [7,19]. Доведено, що при проведенні активного охолодження новонароджені з короткостроковим несприятливим прогнозом ГІЕ (значним ураженням сірої речовини на МРТ) потребували меншої інтенсивності охолодження (вищої температури пристрою для охолодження) для підтримки центральної температури (температури ядра, ректальної температури) в межах 33,0-34,0 °C протягом 72 годин [7].…”
Section: час початку лікувальної гіпотермії та перебіг гіпоксично-ішеunclassified
“…Як короткотермінові критерії несприятливого прогнозу розглядали смерть внаслідок поліорганної недостатності та постішемічного набряку мозку, діагностику деструктивних гіпоксично-ішемічних уражень мозку при нейросонографічному обстеженні. Як додаткові критерії сприятливого короткотермінового прогнозу (у разі відсутності деструктивних гіпоксично-ішемічних уражень мозкової тканини) розглядались відсутність електроенцефалографічних елементів судом, наявність повноцінного перорального харчування [7,20].…”
Section: матеріали та методиunclassified
“…The relationship between disturbances in thermoregulation and prognosis in patients with traumatic brain injury and after cardiac arrest has been proven [18][19][20][21][22][23][24][25][26][27] . Even some simple methods of assessing brain damage in adult patients after cardiac arrest and in newborns after PA have been proposed [28][29][30] . However, these methods result in a Heat Index (HI) 28 and utilize temperature of the cooling water only.…”
Section: Introductionmentioning
confidence: 99%